Electronic structure and spin properties study on 2D h-BN nanosheet with Ti or Fe doping. (February 2020) - Wang, Min; Meng, Fanfan; Hou, Denglu; Han, Yilin; Ren, Jie; Bai, Chenxiang; Wang, Baozhu; Zhou, Tiege
Abstract: The electronic structure and spin properties of Titanium (Ti) or Iron (Fe) doped hexagonal boron nitride ( h -BN) nanosheet have been studied by using ab initio study based on density functional theory (DFT). GGA + U calculations show that one Ti or Fe atom can introduce local magnetic states into the system. Impurity levels will be generated in band gap, and this will lead to spin polarization. The calculated magnetic moments are 1.0 μ B and 2.9 μ B for Ti and Fe, respectively. Furthermore, the magnetic moments are all contributed by the d orbitals of doped atoms in h -BN monolayer. The studies of magnetic coupling reveal that two Ti atoms are mainly coupled antiferromagnetically at different distances between Ti atoms in h -BN monolayer. The Ti-doped system is coupled ferromagnetically only when Ti–Ti distance is 6.625 Å. While the magnetic coupling exhibits regular oscillation characteristics in the system with two Fe atoms doping at different distances. This novel property in Fe-doped h -BN nanosheet provides a new way to control the spin property of material. Our research is beneficial to the development of spintronics. Highlights: Magnetism in Ti or Fe-doped h -BN system has been studied by GGA + U method. We show in theory that impurity Ti can't lead to macromagnetism in BN monolayer. The magnetic coupling between Fe atoms at different distances will produce regular oscillation. The novel property in Fe-doped h -BN nanosheet provides a new way to control the spin property of material.